2018
DOI: 10.3390/molecules23051211
|View full text |Cite
|
Sign up to set email alerts
|

β-Phenylalanine Ester Synthesis from Stable β-Keto Ester Substrate Using Engineered ω-Transaminases

Abstract: The successful synthesis of chiral amines from ketones using ω-transaminases has been shown in many cases in the last two decades. In contrast, the amination of β-keto acids is a special and relatively new challenge, as they decompose easily in aqueous solution. To avoid this, transamination of the more stable β-keto esters would be an interesting alternative. For this reason, ω-transaminases were tested in this study, which enabled the transamination of the β-keto ester substrate ethyl benzoylacetate. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…AKU 638 is uncovered. Only recently it was also shown that the ethyl ester of ( R )-PA can be converted by a commercial fold type IV transaminase (ATA117 11Rd), which however has been largely modified and no longer shows a high identity to wild-type ω-TA (Buß et al 2018b ). Therefore, it seems unlikely that such a transaminase can occur in BS115, especially since tests with cell lysate do not indicate any transaminase reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKU 638 is uncovered. Only recently it was also shown that the ethyl ester of ( R )-PA can be converted by a commercial fold type IV transaminase (ATA117 11Rd), which however has been largely modified and no longer shows a high identity to wild-type ω-TA (Buß et al 2018b ). Therefore, it seems unlikely that such a transaminase can occur in BS115, especially since tests with cell lysate do not indicate any transaminase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…After uncovering the degradation pathway of ( S )- and ( R )-β-PA in Paraburkholderia sp., these strains might be optimized for the production of β-PA as has already been shown for several α-amino acid production strains (Sanchez et al 2017 ). The abilities to synthesize ( R )-configurated aromatic amines and amino acids by asymmetric synthesis are limited by the availability of ( R )-selective enzymes; so far, only few plant enzymes are known for the synthesis of ( R )-β-PA (Ratnayake et al 2016 ; Buß et al 2018b ). So the investigation of the ( R )-β-PA degradation process in BS115 might not only lead to a deeper understanding of the biochemical pathways of β-AA but to novel approaches for the chemoenzymatic synthesis of this highly relevant substance class.…”
Section: Discussionmentioning
confidence: 99%
“…In order to circumvent the use of the unstable b-oxoacid, Rudat and co-workers employed a mutated transaminase to convert the corresponding ethyl ester, but the enantiopure L-b-phenylalanine ethyl ester could only be isolated in 9% yield. 374 (S)-3-Amino-3-phenylpropanol can also be converted to maraviroc upon conversion of the alcohol to a good leaving group. 357 Resolution of various protected 3-amino-3-phenylpropanol derivatives could be achieved using either lipase or penicillin G acylase.…”
Section: Scheme 55 Chemoenzymatic Route Towards Oseltamivir As Develomentioning
confidence: 99%
“…As the expression of ω-TAs is growth-associated and essential in nitrogen metabolism, nitrogen plays an important role in the induction of these enzymes (Shin and Kim 2001 ). ( rac )-α-methylbenzylamine (MBA) and o -xylylenediamine (OXD) are promising amine donors to survey ω-TA activity (Buß et al 2018c ; Shin and Kim 2001 ). The former is a model amine donor (Shin and Kim 1997 ) which is converted to acetophenone (AcPhe) after transformation of amine group to ketone during ω-TA activity, then, AcPhe concentration can be quantified (Guo and Berglund 2017 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…OXD is a substrate for most ( R )- and ( S ) - selective ω-TAs that have been assayed so far and can be used as amine donor in combination with a plethora of amine acceptors as demonstrated by Kelly (Kelly et al 2017 ). The OXD colorimetric assay can be applied to high-throughput screening of ω-TAs in liquid phase (Buß et al 2018c ) or recombinant colonies expressing transaminase in solid phase (Green and Turner 2016 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%